2017
DOI: 10.1007/s11295-016-1098-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic diversity and association mapping of nut and kernel traits in Slovenian hazelnut (Corylus avellana) germplasm

Abstract: European hazelnut (Corylus avellana L.), cultivated in several areas of the world including Europe, Anatolia, and the USA, is an economically important nut crop due to its high mineral, oleic acid, amino acid, and phenolic compound content and pleasant flavor. This study examined molecular genetic diversity and population structure of 54 wild accessions and 48 cultivars from the Slovenian national hazelnut collection using amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…Beltramo et al (2016) [ 29 ] developed a new linkage map with SSR markers and performed a QTL analysis for vigor, sucker habit, and time of budburst. Recently, Özturk et al (2017) [ 30 ] applied association mapping for nut and kernel traits in Slovenian hazelnut germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Beltramo et al (2016) [ 29 ] developed a new linkage map with SSR markers and performed a QTL analysis for vigor, sucker habit, and time of budburst. Recently, Özturk et al (2017) [ 30 ] applied association mapping for nut and kernel traits in Slovenian hazelnut germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The 30 SSR markers provided sufficient polymorphism in the 402 hazelnut accessions with 13.6 fragments per marker. This value is slightly higher than those obtained by others using SSR markers in hazelnut which varied from 3 to 10.6 fragments per primer pair (Bassil et al 2005;Boccacci et al 2005Boccacci et al , 2008Gökirmak et al 2009;Boccacci and Botta 2010;Gurcan and Mehlenbacher, 2010;Gurcan et al 2010a, b;Campa et al 2011;Bassil et al 2013;Ozturk et al, 2017). In previous work, a higher annealing temperature was used for these SSR primers (Gurcan et al, 2010a) (60 rather than 55°C).…”
Section: Marker Polymorphismmentioning
confidence: 65%
“…In another study, 275 F1 hybrids of 'Tonda Gentile delle Langhe' × 'Merveille de Bollwiller' hazelnut trees were used for quantitative trait locus (QTL) identification for traits such as vigor, sucker habit, and time of bud burst (Beltramo et al 2016). In the most recent study, kernel and nut shape traits were examined in Slovenian hazelnuts and the QTL for these traits were detected using SSR markers and association mapping analysis (Ozturk et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Akın et al (2016) identified a set of 14 primer pairs for pre-PCR multiplexing, further simplifying and reducing the cost of the procedure. More than 900 polymorphic SSR markers have been developed in C. avellana (Bassil et al, 2005a(Bassil et al, ,b, 2013Boccacci et al, 2005Boccacci et al, , 2015; Gürcan and Mehlenbacher, 2010a,b;Gürcan et al, 2010;Mehlenbacher, 2017, 2018;Colburn et al, 2017;Öztürk et al, 2017;Zhao et al, 2019;Kavas et al, 2020;Hill et al, 2021;Şekerli et al, 2021) of which ∼450 have been placed on the reference linkage map (Mehlenbacher et al, 2006;Mehlenbacher and Bhattarai, 2018).…”
Section: Introductionmentioning
confidence: 99%